Surgical Intervention for Endobronchial Tuberculosis with Total Bronchial Occlusion: A Case Report - Putra, Muhammad A; Billy, Matthew; Ardaya, Radhyaksa; Ekasiwi, Rut HP; Rahmawati, Sari; Sumarsudi, Karel HS (The New Ropanasuri Journal of Surgery, 2022)
Introduction. Endobronchial Tuberculosis (EBTB) is a specific TB form affecting the tracheobronchial tree with microbial and histopathological evidence. Early diagnosis is essential to provide timely treatment and prevent complications but also proves difficult due to the low positive rate of acid–fast bacilli (AFB) staining of sputum smears and non–specific clinical and radiological findings. Case Illustration. We reported a 19–year–old man with a productive cough suspected of pulmonary tuberculosis, with a positive GeneXpert test and negative AFB smear. He received anti–tuberculosis drugs for six months. Although the symptoms initially seemed to improve, the patient complained of dyspnea during moderate activities in the sixth month. Chest x–ray showed complete atelectasis of the left lung. Further investigation with thorax computed tomography and confirmation with bronchoscopy revealed total occlusion of the left main bronchus. Left pneumonectomy was successfully conducted. Conclusion. Endobronchial tuberculosis may progress to an advanced stage despite adequate anti–tuberculosis drugs. Therefore, early diagnostic strategies are required to prevent the progression of the disease, particularly due to the insidious nature of its pathophysiological process